Social implications of agent-based planning support for human teams - Jiang, Wenchao; Fischer, Joel E.; Greenhalgh, Chris; Ramchurn, Sarvapali D.; Wu, Feng; Jennings, Nicholas R.; Rodden, Tom (2014)
We present a field trial of how instructions from an intelligent planning agent are dealt with by distributed human teams, in a time-critical task setting created through a mixed-reality game. We conduct interaction analysis to examine video recorded field observations and game log data. The findings highlight the social process by which players interpret and negotiate the agent guidance as well as how these are intertwined with social dynamics of the teams. The insights can be used to develop an understanding of interactional issues around automated team instructions and inform the design of human-centred planning support systems.